(untitled) (Práxis Educativa, 2022)
In this work, we present a discussion on the issue of the relationship between the mentee/the mentor in the guidance processes in the context of a Master’s course. On the one hand, the crossroads of this text is to address the tensions and violence that occur in these relationships, often characterized as manifestations of racism. On the other hand, we also address the possibility of this relationship to reconfigure healing spaces and scientific-affective partnerships. We mobilize methodological paths that combine the results of studies, reflections and escrevivências, which point to the importance of tensioning colonialist epistemologies and behaviors based on the western scientific perspective of thinking about the academic context so that orientation relationships can move towards more humanized references and ancestral encounters. Keywords: Racisms. Guidance. Decolonialities.